Smart Glove Sebagai Alat Bantu Komunikasi Pasien - Gilang Wiranda; Agus Urip A Agus Urip A; Putri Madona (Politeknik Caltex Riau, 2023)
Therapeutic communication in nursing is the process of communication conducted by a nurse while carrying out nursing interventions, with the aim of providing therapeutic benefits in the patient's healing process. In therapeutic communication, a nurse can gain a deep understanding of the condition of the patient being treated and decide on the most appropriate nursing actions. This is to ensure that the care provided is tailored to the patient's needs, thereby helping to expedite the healing process. A nurse-call device, also known as